Domestication of Trees for Agroforestry in Drylands - Leaky, R R.B; Wilson, J; Deans, J D (Annals of Arid Zone, 2016)
With regard to drylands, this paper reviews the recent increased interest in enhancing firstly the production of tree products (particularly non-wood products) through the domestication of indigenous trees, and secondly the environmental services arising from their cultivation. A consideration of the purpose of tree domestication looks at the possible benefits to farmers in terms of increasing farmer income and their food and nutritional security. It also examines the special requirements for tree domestication in drylands and the better use of natural resources through agroforestry. Currently, tree domestication in drylands is at an early stage. For example, in the Sahel, priority tree species have recently been identified and germ plasm collection initiated. Similar steps have also been taken in southern Africa where some genetic selection has commenced in indigenous fruit trees. Elsewhere, notably in Kenya, studies have examined the tree-crop-soil interactions (especially the competition for water) in simple agroforestry systems. In recent years, agroforestry interest in dry lands has shifted back towards the more traditional practice of integrating crops, shrubs and other trees within widely spaced mature trees producing fruits and other products, which form a mature stage agroecosystem or multistrata agroforesCUnlike modern intercropping systems, this appears to mimic natural ecosystems and may represent a more sustainable form of productive landuse than intensive tree cultivation, which is particularly detrimental to water resources. Tree domestication, therefore, has the potential to enhance the economic benefits of agroforestry for farmers, while at the same time, promoting an agroforestry strategy that optimizes the interactions between trees and crops.